ANALISIS KESTABILAN LERENG PADA SEKITARAN LUBANG BMK 35 DI CV. BARA MITRA KENCANA (BMK), TANAH KUNING, DESA BATU TANJUNG, KECAMATAN TALAWI, KOTA SAWAHLUNTO - Eggi Marcelleno; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2021)
Based on the results of observations at BMK 35 CV. Bara Mitra Kencana, the authors conducted research on BMK 35 slopes where slope height (H) = 35 m and slope (a) = 65°. Referring to the description of the BMK 35 supervisor, in mid-2018 a large landslide occurred which resulted in tunnel 1 and tunnel 3 being completely buried. As a result of this incident, BMK 35 stopped producing for half a year due to road and tunnel access improvements. This incident occurred due to rainy weather at the mine site in mid-2018 and the absence of a good geotechnical design for the BMK 35 slope. Based on the data from the physical and mechanical properties of rock, the siltstone natural density was 22,84 KN / m³, the saturated density was 23,79 KN/m3, the dry density value was 20,17 KN / m3, cohesion (c) = 0.0419 Mpa and internal friction angle (ϕ) = 44,45°. In determining the value of the actual slope safety factor using software rocscience slide 6.0 with the janbu simplified method, the saturated condition slope safety factor value is 1,192, natural condition is 1,209 and dry condition is 1,265. So it can be concluded that the slope is unstable. The author provides two recommendations for slope improvement, namely, single slope and overall slope. Recommendations with a single slope is use a slope height of 35 meters, angle of slope 58° and get a FK 1,318 in natural conditions, 1,300 in saturated conditions, 1,375 in dry conditions. Recommendation overall slope is to divide into 2 single slope where each slopes have heights 17.5 meters and angle of the single slope is 65° and 51° for the overall slope. When in natural conditions, FK on a single slope is 1,559 and 1,403 for the overall slope. When conditions are saturated, FK on a single slope is 1,529 and 1,384 for the overall slope. When conditions are dry, FK on a single slope is 1,656 and 1,464 for the overall slope.